Pengaruh Strategi Konversi Peta Konsep Terhadap Retensi Mahasiswa Jurusan Pendidikan IPA Biologi Universitas Islam Negeri Mataram - Agustiningsih, Neneng (Magister Pendidikan Biologi, Universitas Negeri Medan, 2017)
This study aims to examine the effect of mind map conversion strategy toward students retention of Biology Education Department in UIN Mataram, year 2016-2017. This research is a Quasi Experiment, using non equivalent control group design with pretest âposttest which performed in two groups of the fourth semester students. Treatment group is class C used mind map conversion strategy, and as control group is class D used a multistrategy, with total of 63 students. The retention instrument uses a mind map scoring sheet. The retention hypothesis was analyzed using t-test by SPSS version 21. The statistical analysis showed sig.t test = 0,00 < 0,05 then H0 is rejected. This mind map conversion strategy has a significant influence toward the retention of class C students.